Is there a Need for Harmonizing Capital Income Taxes within EC Countries? (IMF Working Papers; Working Paper, 1990)
This paper describes how growing economic integration within the European Community increases the scope for any one EC country to impose adverse externalities on other member countries by manipulating its capital income taxes. After examining several alternatives to concerted tax harmonization, the paper concludes that there is a need to harmonize capital income taxes within the EC as the Community moves toward a unified market with free capital movements and fixed nominal exchange rates. The harmonization process could start by agreeing on the tax base, followed by setting minimum statutory rates.